TOWARD A THEORETICAL INQUIRY INTO CODESWITCHING: THE INDONESIAN EXPERIENCE - Gunawan, Samuel (k@ta: A Biannual Publication on the Study of Language and Literature, 2005)
Hardly has codeswitching been evaluatively treated on the theoretical level using the natural language data from the sociolinguistic context of Indonesia. This research paper is to address such an issue as a field of inquiry incorporating the researcher’s first-hand encounter with naturalistic language data in the field.